Penyebarluasan Informasi Peringatan Dini Bencana Banjir di Kantor Kelurahan Kemuning Banjarbaru - Marhaeni Fajar Kurniati; Periyadi Periyadi; Ariansyah Ariansyah; Eirlin Febriana; Hernida Rahmadina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Floods are disasters that often occur in Indonesia. Disasters caused by hydrometeorological factors always increase every year. Even though sometimes it doesn't cause many casualties, this disaster still damages infrastructure and significantly disrupts the economic stability of the community. The characteristics of floods are very diverse, floods can be caused by high rainfall without adequate soil absorption or can occur in the form of flash irrigation failures. South Kalimantan is a city known as the